The Importance of Cooperation between Preschool Education and Primary Education - Bisenbaeva Aray Kuralbay kizi; Tuzikenova Juldizay Amantaevna (International Journal on Integrated Education, 2022)
This article emphasizes the importance of the connection between preschool and primary education. It also examines the scientific ideas of Eastern researchers, as well as crucial features of cooperation and the peculiarities of preschool and primary school education in modern Uzbekistan